1988
DOI: 10.1210/mend-2-3-217
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Messenger Ribonucleic Acid in the Developing Human Placenta and in Term Placenta of Diabetics

Abstract: Fetal growth and development are dependent upon the growth and development of the placenta. Control of placental growth and development is little understood. Immunoreactive insulin-like growth factor-I and -II (IGF-I and IGF-II) have been shown to be released by human placental tissue and human placental membranes have been observed to contain specific receptors for these growth factors. Furthermore, we have demonstrated the presence of IGF-II mRNA transcripts in the developing human placenta and at gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 88 publications
3
29
0
Order By: Relevance
“…During early and mid gestation, the placental expression of IGF-I mRNA is greater than in late pregnancy (24,25), suggesting that IGF-I plays an important role in early placental development as a placental growth factor (25). Placental IGF-I expression is mainly localized to the maternal stroma (12), and although statistical comparison between the two tissue types is not possible, our data support previous localization observations.…”
supporting
confidence: 87%
“…During early and mid gestation, the placental expression of IGF-I mRNA is greater than in late pregnancy (24,25), suggesting that IGF-I plays an important role in early placental development as a placental growth factor (25). Placental IGF-I expression is mainly localized to the maternal stroma (12), and although statistical comparison between the two tissue types is not possible, our data support previous localization observations.…”
supporting
confidence: 87%
“…Although not all reports are consistent, in the baboon, rhesus monkey, and human, the IGF-1R, IGF-1, and IGF-2 have all been localized to the cellular layers of placenta, including the continuous layer of cytotrophoblasts, the protective barrier layer of multi-nucleated syncytiotrophoblasts, and to the maternal decidual membranes, depending on the stage of gestation (Coulter and Han, 1996;Dhara et al, 2001;Han et al, 1996;HildPetito et al, 1994;Wang et al, 1988). Maternal IGF-1 and IGF-2 levels change only modestly if at all throughout gestation Tarantal and Gargosky, 1995), except during implantation when maternal IGF-2 levels increase dramatically (Dhara et al, 2001).…”
Section: Igf Localization During Pregnancymentioning
confidence: 99%
“…Both IGFs-I and -II are synthesized in the placenta (6,7). As the localization of IGFs and IGFBPs was similar, it was suggested that the IGFBPs regulated IGFs within the placenta (8).…”
Section: Introductionmentioning
confidence: 99%